Perancangan Aplikasi E-commerce Penjualan Bubuk Kopi Dengan Metode Customer Satisfaction Index (CSI) Berbasis Website Pada UD. Tanpak Sidikalang - Samuel Manurung; Ingngarso Simanullang; Humuntal Rumapea (Journal of Information and Technology, 2022)
The development of e-commerce at this time is increasingly rapidly marked by the increasing number of internet users in Indonesia. The conventional buying and selling process is still widely used in the era of increasingly rapid development of internet technology. However, the conventional buying and selling process is considered inefficient because it requires sellers and buyers to meet directly and also the sales coverage is felt to be less broad, so an efficient sales media is needed and has a broad coverage. So that these problems are not sustainable, an e-commerce website with a business to customer model will be built. The built e-commerce will provide a questionnaire page for customers which will later be implemented by the customer satisfaction index (CSI) method which produces a customer satisfaction index for the e-commerce that has been built. For software development, using PHP (Pear Hypertext Preprocessor) and HTML (HyperText Markup Language) as programming languages, MySQL as database server, Sublime Text 3 as programming support tools